Phosphorus fertilization and seeding rate effects on sulla (Hedysarum coronarium L.) forage production - Anastasi U.; Santonoceto C. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A pluriannual experiment was conducted in a hilly area of southern Italy with the aim of evaluating the response of sulla to phosphorus fertilization and seeding rate. Two different fields both maintained for two productive cycles were sown to study the effects of three fertilizers - 50, 100 and 150 kg ha-1 of P2O5, respectively and a non fertilized control, in a factorial combination with three seeding rates - 25, 50 and 75 kg ha-1 of seed respectively. Variations in dry weight and leaf area per plant as a result of the experimental factors were observed as the growing season progressed: the values of both traits increased significantly with the amount of P-fertilizer supplied to the soil and with the reduction in seeding rate. The supply of P-fertilizer up to 100 Kg ha-1 of P2O5 resulted in significant increases in dry matter yield compared to the non fertilized control, in particular in the later growth phase of the meadow.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)